Subset of DN Memory B Cells Expressing Low Levels of Inhibitory Receptor BTLA Is Enriched in SLE Patients - Lucie Aubergeon; Renaud Felten; Jacques-Eric Gottenberg; Hélène Dumortier; Fanny Monneaux (Cells)
The dialogue between T and B cells can be regulated by different mechanisms, such as co-inhibitory receptors, which therefore play a crucial role in preventing autoimmune diseases such as systemic lupus erythematosus (SLE). B and T lymphocyte attenuator (BTLA) is a co-inhibitory receptor expressed on many myeloid and lymphoid cells. Although peripheral B cells express a very high amount of BTLA, previous works in the context of autoimmunity mainly focused on T cells, and whether BTLA expression on B cells plays a role in the lupus pathogenesis is still unclear. In the present study, we examine the expression of BTLA, as well as its ligand HVEM (Herpesvirus Entry Mediator), on various B cell subsets in lupus patients compared to healthy controls (HCs). We evidenced the existence of double-negative (DN; IgD−CD27−) memory B cells expressing very low levels of BTLA, which are enhanced in active lupus patients. An in-depth analysis revealed that these BTLAlow DN cells mainly correspond to the newly reported DN3 B cell subset, originally described in the context of SARS-CoV2 infection. These cells display an activated and antibody-secreting cell phenotype, and we propose that their low BTLA expression may favor their expansion and rapid differentiation into plasmablasts in lupus patients.